S04.3 Antiretroviral Therapy Among Female Sex Workers in Burkina Faso: Current Situation. (13th July 2013) - Konate, I; Ouédraogo, A; Bazié, W W; Traoré, I T; Sanon, A; Huet, C; Méda, N; Mayaud, P; Perre, P Van De; Nagot, N
Abstract : Background: In Burkina Faso, female sex workers (FSW) are a core group in HIV transmission with 16.5% cases of HIV-infection, vs. 1.0% in the general population. Provision of ART to this core group may be key to controlling the HIV epidemic. We aimed at documenting the current situation regarding ART provision to FSW in Burkina Faso. Methods: We reviewed the interventions of the national HIV/AIDS control programme (NACP) regarding ART provision to FSW, using grey literature and interviews of stakeholders. In addition, we reviewed the findings of the local research on this topic. Results: Before 2010, programmes targeting FSW in Burkina Faso focused only on prevention, mainly through local NGOs. From 2010, in each of the 13 regions, the NACP designated one primary health centre to care for FSW. No statistics are available yet from these centres, but NACP/MOH stakeholders admitted that few FSW adhere to it, mainly because of a lack of strategy to reach and retain FSW, and lack of health care workers training. The ANRS 1222 "Yerelon" research programme tested a FSW peer-led intervention integrating prevention and care activities within one dedicated centre in Bobo-Dioulasso. Beside care providers, peers and a psychologist much contributed to support ART adherence before and after initiation. Preliminary data among the 47 FSW treated with ART showed high adherence to ART (> 95%) at 12 months (92%) and 36 months (100%). At 36 months, plasma viral load was undetectable in 82% of FSW, with a mean CD4 increase of 230 cells/µL (IQR: 90–400). Conclusion: Despite a specific programme, ART provision to FSW remains limited in Burkina Faso. The 'Yerelon' model of prevention and care intervention can serve as a strategy for the NACP FSW programme, and the research sites be used as training centres to improve ART provision coverage and efficiency.